Pengembangan Paket dan Strategi Pembelajaran IPA melalui Permainan Tradisional untuk Siswa Kelas 3 SD di Daerah Rawan Bencana Studi Kasus di SD Puncak Manis, Kecamatan Kadudampit, Sukabumi - Sri Tatminingsih; Sudarwo -- (Jurnal Pendidikan dan Kebudayaan, 2012)
This research aims to identify traditional games and the characteristics of thirdgrade elementary school students, as well as to develop packages and learning strategies thatÂ are appropriate for third grade elementary school students in the disaster-prone area in WestÂ Java Province. This study employed research and development as the research design by usingÂ third grade students and teachers in elementary school Puncak Manis as well as the communityÂ of district Kadudampit, Sukabumi in West Java as the samples. Interviews and observation were used as data collection techniques. The results showed that almost all students are notÂ familiar with the games, but there are some traditional games that are still known by theÂ community of district Kadudampit such as Oray-orayan, Cing Ciripit, Pacici Putri, Sonda andÂ Egrang. The characteristics of elementary school students in the area of disaster-prone areÂ generally passive, dependent on teachers and less creative. Learning packages in a form ofÂ printed or picture books and videos that are appropriate for the third grade elementary schoolÂ students in disaster-prone areas were delivered through traditional games as the strategy. TheÂ try out results showed an increase in studentsâ€™ understanding of science teaching materialsÂ especially for the topics of â€œfloodâ€ that is 0.58 and for â€œearthquakeâ€ that is 0.76. This suggestsÂ that the use of the learning package in the form of booklets and books students on material related to disaster mitigation and sanitation floods and earthquakes which are delivered through traditional games (like Oray-orayan, Ciripit and Cing Pacici-cici Putri) assisted students in understanding the material about mitigation and sanitation related floods and earthquakes.Â ABSTRAKÂ Penelitian ini bertujuan untuk mengidentifikasi permainan tradisional, karakteristik, dan mengembangkan ujicoba paket dan strategi pembelajaran kelas 3 SD di wilayah rawan bencana di Propinsi Jawa Barat. Sampel penelitian terdiri atas siswa dan guru kelas 3 di SDN Puncak Manis dan Pemuka masyarakat di Kecamatan Kedungpi, Kabupaten Sukabumi Jawa Barat. Teknik pengumpulan data dengan wawancara dan observasi. Hasil penelitian menunjukkan bahwa hampir semua siswa tidak mengenal permainan tradisional di wilayahnya, namun terdapat beberapa permainan tradisional yang masih dikenal oleh masyarakat di Kecamatan Kadudampit, di antaranya Oray-orayan, Cing Ciripit, Pacici Putri, Sonda dan Egrang. Karakterisitik siswa SD di daerah rawan bencana umumnya pasif dan kurang kreatif, bergantung Â pada Â guru. Paket pembelajaran yang sesuai siswa kelas 3 SD di wilayah Â rawan bencana berupa bahan ajar cetak, buku bergambar, dan video. Hasil ujicoba menunjukkan adanya peningkatan pemahaman siswa terhadap materi pembelajaran IPA untuk materi banjir sebesar 0,58 dan untuk Â materi gempa bumi sebesar 0,76. Hal ini menunjukkan bahwa penggunaan paket pembelajaran yang berupa booklet Â dan buku siswa tentang materi mitigasi dan sanitasi terkait dengan bencana banjir dan gempa bumi yang disampaikan Â melalui Â permainan Â tradisional membantu siswa dalam memahami materi tersebut.